Attitudes and beliefs towards mental disorders - Sturla Brynjólfsson 1988- (2016)
The aim of this study was to get a better understanding of which variables affect attitude towards mental disorders. Of special interest was to explore how familiarity with mental disorders affected attitude. Participants were 218 students at Reykjavík University. Prejudice towards mental disorders was rather low among participants. Results revealed that there is a significant inverse relationship between familiarity and prejudice, both having a family member diagnosed with a mental disorder (β = -.150, p < 0,05) and a friend diagnosed with a mental disorder (β = -.174, p < 0,01), when all other variables had been accounted for. These findings further address the issue individuals with mental disorders are facing, stigmatization and social distancing. This study data could add further realization for the need for campaigns being created that increase proximity with individuals with mental disorders. Tilgangur rannsóknarinnar var að ná betri skilning á hvaða breytur hefðu áhrif á viðhorf til geðraskana. Sérstakur áhugi var að athuga hvernig nánd við einhvern með geðröskun hefði áhrif á viðhorfið. Þátttakendur voru 218 nemendur við Háskólann í Reykjavík. Fordómar gagnvart geðröskunum var almennt lágt meðal þátttakenda. Niðurstöður sýndu fram á marktækt gagnstætt samband milli nándar og fordóma, bæði það að eiga fjölskyldumeðlim greindan með geðröskun (β = -.150, p < 0,05) og vin greindan með geðröskun (β = -.174, p < 0,01). Þessar niðurstöður varpa enn frekara ljósi á þá fordóma sem einstaklingar með geðraskanir glíma við. Rannsóknin gæti leitt huga fólks að því hve mikilvæg nánd við geðraskanir raunverulega er. Helst er þessi vitneskja mikilvæg herferðum þar sem megin tilgangur er að uppræta fordóma gagnvart geðröskunum.